Transatlantic discourse on integration - The Migration-Security Nexus in the light of the German EU-presidency: a conference report - Bosch, Nicole; Wiest, Delia (2007)
Abstract: Contents: 1. Introduction; 2. Contents of the Workshop; 2.1. Security Measures in Germany and the U.S. – Securitizing Migration Policy?; 2.2. Security and its Relevance for Migration Affairs; 2.3. Comments on Situation of Muslims in the U.S., Germany and Europe; 2.4. Security in the EU – Where do we go?